How to cheat in Photoshop CS3 : the art of creating realistic photomontages - Caplin, Steve (Focal Press, an imprint of Elsevier, 2007)
* New! Zip through the learning curve in a snap with the free DVD! * Hundreds of new Photo Objects, companion project files, QuickTime movie tutorials, sample plugins, and more. * Don't miss the website www.howtocheatinphotoshop.com where the author answers your reader questions directly!When you're short on time with crunching deadlines, but there's no way you can sacrifice quality, this book/DVD comes to the rescue. Nobody knows more about how to work fast under pressure and still produce top-notch photographic images than hands.